Neurofibroma of the breast in a boy with neurofibromatosis type 1 - Murat, A; Kansiz, F; Kabakus, N; Kazez, A; Ozercan, R (Elsevier Science Inc, 2004)
Neurofibromas occurring in the breast are very rare. A 10-year-old boy with neurofibromatosis type 1 (NF1) presented with a palpable mass on his left breast. US showed a well-defined and hypoechoic solid mass within the subcutaneous fat tissue in the areolar area. Mass was isointense compared to muscle and hypointense compared to fat tissue on TIW and T2W MR images. Excisional biopsy was applied to the mass. The diagnosis of gynecomastia and neurofibroma was made on the basis of histopathological and immunohistochemical findings. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: breast; neurofibromatosis; children